2017
DOI: 10.4081/vl.2017.6627
|View full text |Cite
|
Sign up to set email alerts
|

An innovative compression system providing low, sustained resting pressure and high, efficient working pressure

Abstract: Not available

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…18 Such high pressures exceeding the intravenous pressure values during movement can only be achieved by inelastic, stiff compression material, showing high pressure peaks during walking and, at the same time, tolerable resting pressures. Sticking patches of hook material on these elastic bandages with a well defined resting pressure, transforms the compression device into a stiff, inelastic system that can maintain a tolerable resting pressure of 20e30 mmHg for up to 1 week, 11 but provides standing pressures of around 60 mmHg and high pressure amplitudes while walking (the so called massaging effect). Theoretically, similar effects could also be produced by wrapping an adhesive bandage over the basic bandage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 Such high pressures exceeding the intravenous pressure values during movement can only be achieved by inelastic, stiff compression material, showing high pressure peaks during walking and, at the same time, tolerable resting pressures. Sticking patches of hook material on these elastic bandages with a well defined resting pressure, transforms the compression device into a stiff, inelastic system that can maintain a tolerable resting pressure of 20e30 mmHg for up to 1 week, 11 but provides standing pressures of around 60 mmHg and high pressure amplitudes while walking (the so called massaging effect). Theoretically, similar effects could also be produced by wrapping an adhesive bandage over the basic bandage.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to this, the new system keeps the CP constant for several days. 11 Different experimental studies in the past have demonstrated that a pressure of around 60 mmHg in the upright position together with the massaging effect at calf level reduce venous reflux 19,20 and ambulatory venous hypertension, 21 thereby enhancing the efficacy of the venous calf pump. 8,9 Bandages applied with higher pressure over the calf could also be shown to reveal stronger beneficial effects on the calf muscle pump.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To a lesser extent, it also depends on elastic properties of the bandage and the number of layers. Furthermore, as the leg circumference decreases, it is more difficult to maintain constant interface pressure, which is why it (and, as a result, the effective compression dose, as well) cannot be precisely determined in most cases [14,[26][27][28]. On the other hand, the intermittent pneumatic compression (IPC) devices offer predefined compression and interface pressure.…”
Section: Interface Pressurementioning
confidence: 99%
“…It consists of two components, the Lundatex ® medical bandage, which provides a safe and well-defined resting pressure owing to a cross-line indicator system, and two velcro products called PressPatch™ and FixPatch™. Adding stiff velcro products not only turns an elastic bandage into an inelastic compression device, but also enables hassle-free maintenance of target interface pressure by readjusting the FixPatch, without the need to re-bandage [ 19 , 26 ].…”
Section: Interface Pressurementioning
confidence: 99%